STUDY ASCERTAINING THE LEVEL OF EMPLOYEE TRAINING IN SECURITY AND PROTECTION COMPANIES - Ţăpoi F.; "Vasile Alecsandri" University of Bacău (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
Most combatants have been or are still champions, world vice champions, national or Balkan champions, or they are practitioners of different sports: martial arts, kayaking - canoeing, athletics, Greek-Roman wrestling, etc. Psychic endurance and stability, presence of mind and fighting ability, supplemented by a higher level of physical training, shape a fighter profile. For this we initiated a study on a total of 20 subjects aged between 36 and 43 years, they work in a company security and protection. For this study we used, tests for assessing physical training and tests for assessing the capacity for adaptation to effort. The results highlight the difference between the levels of training of subjects included in this research. The conclusions validate the hypothesis that components and ordinne and security firms have a good level of physical preparation medium